Perancangan Assesmen Literasi Kimia Pada Materi Termokimia Kelas XI SMA/MA - Silfiyani Afifah; Eka Yusmaita (Universitas Negeri Padang, 2019)
Chemical literacy is a basic ability to obtain the basic concepts of chemistry macroscopically, microscopically and symbolically as well as the process for understanding and describing phenomena scientifically. This study aims to create an instrument to measure the assessment of chemical literacy in high schools on thermochemical material. The design of this study uses the Model of Educational Reconstruction (MER). The stages of this research include: content structure analysis (curriculum analysis, material content analysis, and context analysis); empirical inquiry (approval by subject matter expert for the instrument designed). Content validity data acquisition is calculated using the Aiken’s V. formula. This formula is used for the assessment of the scale of politics (scale 1 to scale 5) in determining the content validity of an item. The results of the validation of the content of chemical literacy questions are 0.85 with a “valid” decision.